Pengaruh Prinsip-Prinsip Good Governance pada Kinerja Keuangan LPD di Kabupaten Karangasem - Yanti, Luh Ade Kusuma; Ary Wirajaya, I Gde (E-Jurnal Akuntansi, 2020)
The purpose of this study was to determine the effect of the principles of good governance on LPD financial performance in Karangasem Regency. The location of the study was conducted at the LPD in Karangasem Regency. The sampling method is purposive sampling technique. Samples obtained were as many as 90 LPD. Financial performance is measured using LPD financial statements from 2016-2018. Good governance principles are measured using statements in the questionnaire distributed to the sample LPD. Technical analysis uses multiple linear regression analysis. Based on the test results obtained that the principles of good governance, namely transparency, accountability, responsibility, independence, and reasonableness have a positive effect on LPD financial performance in Karangasem Regency. Keywords: Good Governance; Financial Performance; Village Credit Institutions.